2004
DOI: 10.1111/j.1572-0241.2004.04085.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interferon Treatment Response on Liver Complications of Chronic Hepatitis C: 9-year Follow-Up Study

Abstract: Response to antiviral therapy, and particularly SVR, appears to reduce liver complications in chronic hepatitis C. However, in the absence of an antiviral treatment response, a course of interferon does not reduce risks of liver cancer or liver failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 44 publications
1
44
1
Order By: Relevance
“…However, after adjustment for the fibrosis score, serum albumin concentration, and mode of transmission in a multivariate model, treatment response failed to reach significance (P ϭ 0.058) as a predictor of outcome. 11 Another multinational cohort study analyzed 479 consecutive patients with chronic hepatitis C with advanced fibrosis or cirrhosis that was treated with IFN or PEG-IFN with or without ribavirin. The authors found that SVR was associated 18 ( with a statistically significant reduction in the hazard of clinical events, mainly liver failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after adjustment for the fibrosis score, serum albumin concentration, and mode of transmission in a multivariate model, treatment response failed to reach significance (P ϭ 0.058) as a predictor of outcome. 11 Another multinational cohort study analyzed 479 consecutive patients with chronic hepatitis C with advanced fibrosis or cirrhosis that was treated with IFN or PEG-IFN with or without ribavirin. The authors found that SVR was associated 18 ( with a statistically significant reduction in the hazard of clinical events, mainly liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 For this reason, all HIVinfected individuals with positive HCV RNA determinations should be considered as candidates for anti-HCVtreatment, providing HIV infection is wellcontrolled and there are no contraindications to therapy with interferon or ribavirin. [7][8][9][10] It is known that response to antiviral therapy appears to reduce liver complications in chronic hepatitis C 11,12 ; however, little is known about the clinical consequences of achieving a sustained virological response (SVR) following therapy with interferon plus ribavirin in coinfected patients. Our objective was to determine the effect of achieving an SVR on clinical outcomes including mortality and liver-related complications in patients coinfected with HIV/HCV.…”
Section: H Uman Immunodeficiency Virus (Hiv) Infectionmentioning
confidence: 99%
“…Interferon therapy, particularly when sustained virological response is achieved, seems to lead to a better hepatic outcome in HCV-monoinfected patients. 24,25 In coinfected subjects with sustained virological response, hepatic decompensations are seen very uncommonly. 10 Therefore, the findings of this study concerning this topic are in line with those found in monoinfected patients and with the few data available in HCV/ HIV coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The only study suggesting a cause-effect relationship between IFN, HCV eradication and the prevention of clinical decompensation did not conduct separate analyses for patients with cirrhosis versus those with chronic hepatitis. 24 Indeed, it is expected that IFN therapy might also lower the risk of HCC in patients with chronic HCV infection, since this drug combines antiviral and antiproliferative properties. Although IFN therapy prevented HCC in selected, it is not clear whether or not the achievement of a SVR might lower the risk of liver cancer in patients with complete cirrhosis.…”
Section: Discussionmentioning
confidence: 99%